MOBIL TELEFON NURLANISHINING INSON SOG‘LIG‘IGA TA’SIRI - Nomonova Xurshida Boymurod qizi; Ahmadjonov Nurolloh Ozodbek o`gli; Komilova Barnoxon Salimjon qizi; Fazliddinov Firdavs G`ayratjon o`gli (New modern researchers: modern proposals and solutions, 2025)
In today's world, mobile phones have become an inseparable part of our daily lives. But how does the electromagnetic radiation they emit affect human health? This research explores the potential impact of radiofrequency waves from mobile devices on brain function, sleep quality, heart rhythm, and cancer risk. It also discusses possible long-term health consequences and precautionary measures. The topic is especially relevant as it sheds light on the hidden health risks of modern technology that often go unnoticed.